IMPLEMENTATION ANALYSIS OF SERVICES BASED ON SOCIAL INCLUSION IN THE COMMUNITY OF THE REPUBLIK GUBUK - Inawati, Inawati; Dewi, Amalia Nurma; Martutik, Martutik; Setiawan, Setiawan (Jurnal Diskursus Islam, 2022)
Abstract: This study aims to analyze the form of implementation of social inclusion-based services in the Republic Gubuk Community which is an association of Gubuk Baca in the Jabung area, Malang Regency. The research was conducted using a descriptive qualitative data analysis approach. data sources used primary and secondary data sources obtained through interviews, observation, and literature review. The results of the research show that the activities that are part of the program at the Gubuk Republik Community are a form of social inclusion-based library service which is in line with the concept of social inclusion-based library services developed by Utami and Prasetyo which describes several aspects, namely reading huts as facilitators in developing growth potential. economy, reading huts as a vehicle for problem-solving, reading huts as a center for community activities, and reading huts play an active role in the literacy movement through various activities such as BUMI Gubuk (Hut-Owned Enterprise), teaching thug, People’s Campus, mobile library movement, and others. etc.